STUDI TENTANG SANGGUL LIPEK PANDAN SEBAGAI SANGGUL TRADISIONAL MINANGKABAU - Oktasari, Sherli; Rahmiati, Rahmiati; Yanita, Merita (Journal of Home Economics and Tourism, 2016)
The bun sanggul lipek pandan fading as a traditional bun of Minangkabau, a challenge for researchers to retrace the history of this bun. This research was qualitative historical. The object of this study is the bun lipek pandan, the informants of this study are the people who know about bun sanggul lipek pandan. The techniques of the data collection in this study by using observation, interviews, documentation and technical data triangulation data analysis and data reduction. The results of this study was found that the bun lipek pandan. Lipek pandan malacuik kuduak for Regional Tanah Datar. The bun lipek pandan sunting tusuk(skewers) for coastal regions(region wearing sunting tusuk).Kata kunci : Studi, Sanggul Tradisional, Lipek Pandans